CHAPTER 5 Effect of Water Vapour on the High Temperature Oxidation of Stainless Steels - Somrerk Chandra-ambhorn; Patthranit Wongpromrat; Thammaporn Thublaor; Walairat Chandra-ambhorn (My University, 2020)
This chapter primarily reviews the nature of water vapour when it presents in bulk gas. The change in a ratio between water vapour and corresponding dissociated hydrogen, which determine the thermodynamic stability of the oxide formation, is analysed when the oxidation kinetics are linear and parabolic. When water vapour reaches the solid/gas interface, chromium species volatilisation and oxidation controlled by surface reaction can occur. The adsorbed water vapour can be further incorporated into the oxide possibly in the form of hydrogen defects. The role of these defects on altering the defect structure of the oxide is discussed. Finally, characteristics of the oxide scale on stainless steels formed in the atmosphere containing water vapour are reviewed.
Keywords: Volatilisation; High-Temperature Coating Behaviors